2014
DOI: 10.1155/2014/407348
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Recurrent Cryptococcal Meningoencephalitis in an Immunocompetent Female

Abstract: Cryptococcus neoformans is commonly associated with meningoencephalitis in immunocompromised patients and occasionally in apparently healthy individuals. Duration and regimen of antifungal treatment vary depending on the nature of the host and extent of disease and CNS shunts are placed in persistently elevated intracranial pressures. Recurrence of infection after initial treatment is not uncommon in HIV positive patients, Kaya et al. (2012) and Illnait-zaragozí et al. (2010). We describe a 39-year-old immunoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Of the 46 studies included, 20 were cohorts 4 , 10 , 14 18 , 21 33 and 26 were case reports/series. 12 , 34 58 The cohort studies were divided in 7 two-arm (groups with and without shunt) and 13 one-arm (group with shunt) studies, and their characteristics are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 46 studies included, 20 were cohorts 4 , 10 , 14 18 , 21 33 and 26 were case reports/series. 12 , 34 58 The cohort studies were divided in 7 two-arm (groups with and without shunt) and 13 one-arm (group with shunt) studies, and their characteristics are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…A neurocriptococose consiste em uma infecção do Sistema Nervoso Central (SNC) suscitada pelo fungo encapsulado Cryptococcus sp. (Niknam et al, 2014;Jha et al, 2019). As infecções provocadas por essa espécie são oportunistas, urbanas e frequentemente estão associadas a condições de imunossupressão e à Síndrome da Imunodeficiência Adquirida (AIDS) (Andrade et al, 2018;Murphy et al, 2020).…”
Section: Introductionunclassified
“…As infecções provocadas por essa espécie são oportunistas, urbanas e frequentemente estão associadas a condições de imunossupressão e à Síndrome da Imunodeficiência Adquirida (AIDS) (Andrade et al, 2018;Murphy et al, 2020). Já em pacientes imunocompetentes é considerada rara e pode provocar dúvidas na determinação das causas de doenças meningoencefálicas (Niknam et al, 2014;Jha et al, 2019).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Male predominance was apparent in most of the previous CM studies in different countries [ 1 , 7 10 ], but recently the noticeable increase in female prevalence was seen, as suggested by the decreased male-to-female ratio [ 10 , 11 ]. Until now, several reports have called attention to the female CM patients [ 12 16 ], but no statistical study of these patients was found.…”
Section: Introductionmentioning
confidence: 99%